Summarizing Laboratory Studies of the Chemical Enhanced Oil Recovery Methods on the Core Samples from Kazakhstani Oil - ZhapbasbayevU., Kenzhaliyev B., SoltanbekovaK., Mankhanova A. (International Journal of Advanced Science and Technology, 2020)
Chemical EOR methods are applied to increase the recovery from mature oil fields after traditional water flooding. Article gives brief characteristics to polymer and ASP flooding technologies and present results of laboratory studies. Water being injected into the reservoir with small volume (0,01 – 0,05%) of high-molecular polymer presents viscoelastic behavior. As a result, the coefficient of mobility is greatly reduced and the resistance factor is increased, as well as the coefficient of coverage of the reservoir. Thus, premature breakthrough to production wells is prevented. Alkaline-surfactant-polymer (ASP) flooding is a chemical EOR in which alkali, surfactant and polymer are injected in the form of a rim. The synergistic effect of these three components can improve oil recovery by reducing surface tension and leveling the injectivity profile. Keywords: polymer flooding, ASP flooding, oil displacement rate, surfactant, alkali, EOR methods, filtration experiment.